(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article provides a comprehensive analysis of the problem of endemic goiter in the Aral Sea region as a consequence of the long-term ecological crisis caused by the drying up of the Aral Sea. The author investigates the systemic cause-and-effect relationships between the degradation of the natural environment, the deterioration of the quality of life of the population and the increase in the incidence of iodine-deficiency pathologies. A multi-agency approach to prevention and treatment, including the modernization of regulatory frameworks, educational strategies and health infrastructure.